Implications of Green Land Cover on Urban Temperature in Malang City, Indonesia - Kusumadewi, Tarranita; Husna, Ana Ziyadatul; Faqihuddin, Mohammad Imam; Mutiara, Elok; Kurniawaty, Prima (Proceedings of the International Conference on Green Technology; Vol 11 No 1 (2021): Proceeding of International Conference on Green TechnologyDO - 10.18860/icgt.v11i1.1525, 2021)
Development in the Malang City area affects changes in land use patterns, one of which is changes in green land cover. Changes in green land cover will impact temperature changes in the area. Therefore, this study was conducted to determine the implications of green land cover changes in Malang urban areas in 2016-2020. This study uses remote sensing technology from Sentinel 2 satellite imagery and band canals to produce a green land density map (NDVI). Next, identify changes in urban temperature that occur. Based on the sensing results, there has been a significant change in land use patterns in the last five years. In addition, it is also known that changes in green land cover have a significant effect on changes in urban temperature, which impact the occurrence of urban heat islands. Thus, the Malang City government, in carrying out development and planning, the Malang City government must pay attention to and consider these changing conditions to minimize the impact of urban microclimate changes so that the city's sustainability is maintained.